Prevalence of risk factors of non-communicable diseases among rural population of Bidar - Tondare, Mahesh B.; Havale, Naveenkumar G.; Bedre, Rahul C.; Kesari, Pallavi (International Journal Of Community Medicine And Public Health, 2017)
Background: The World Health Organization (WHO) global status report on NCDs in 2010 showed that NCDs are the highest leading cause of death over the developed and developing countries. More than 36 million people died from NCDs in 2008 from cardiovascular diseases (48%), cancers (21%), chronic respiratory diseases (12%), and diabetes (3%). Methods: The present study carried out among 2957 rural population in rural field practice area of department of community medicine. Using the WHO STEPS approach, information on risk factors of non-communicable diseases (NCD) like socio demographic, behavioural, physiological and physical measurements were obtained through standardized protocol. Results: Among the 2957 people studied 48.6% were in age group of 15–35 years. 68.1% were having education below secondary/higher secondary. 47.2% belonged to lower middle and 39.6% belonged to lower socioeconomic class. 44.8% of them were either farmers or labour/ unskilled workers. In the studied population 29.93% were currently using tobacco either in the form of chewing or smoking, among these 98.42% were males. 27.29% were currently consuming alcohol, of these males comprised 97.77%. Among the studied population 13.3% were hypertensive and 3.42% were diabetics. Conclusions: In this study majority belonged to lower middle or lower socioeconomic class, with occupation as either farmer or labour/ unskilled workers. Among those who consumed tobacco and alcohol as risk factors for NCD, majority were males. The prevalence of hypertension was more compared to diabetes.